The Effect of STEAM-Based Environmental Learning on Students' Ecoliteracy Level at SDI Hartaco Indah Makassar - M.Ichsan Ali; Asri Ismail; Nurfadila MY (Journal of Innovative and Creativity, 2025)
This study aims to examine the effectiveness of the STEAM learning model in improving the ecoliteracy skills of elementary school students, with the hypothesis that this interdisciplinary approach can have a significant effect on students' knowledge, attitudes, cognitive skills, and pro-environmental behavior. The study used a quantitative approach with a one group pretest-posttest type pre-experiment design. The research location was at SDI Hartaco Indah Makassar, with a sample size of 25 students selected purposively. Data collection instruments include pretest and posttest tests, observation sheets, and student questionnaires, which have been validated through expert judgment and tested for reliability with Cronbach's Alpha. Data analysis was done descriptively and inferentially, including normality test and paired sample t-test. The results showed a significant increase in all indicators of student ecoliteracy with a significance value of 0.000 (p < 0.05), as well as an average N-Gain value of 0.627 which is classified as a moderate category. This finding indicates that STEAM-based learning is able to integrate elements of science, technology, engineering, art, and mathematics in a contextual manner to shape students' ecological awareness and behavior. The implications of this study support the importance of developing interdisciplinary learning models in elementary schools as a strategy to strengthen applicable and sustainable environmental education.